Significance of Creatinine and Cystatin-S Values in Early Diagnosis of Renal Dysfunction in Cardiorenal Syndrome - Khalilova Feruza Abdujalolovna (American Journal of Biomedicine and Pharmacy, 2025)
It is known that, according to generally accepted principles, early diagnosis of kidney dysfunction in cardiorenal syndrome uses calculated glomerular filtration rate (hCFT) determined on the basis of creatinine and cystatin-S indicators. However, a number of scientific studies have shown that the decrease in hKFT is observed much later than the appearance of tubulo-interstitial changes in the kidneys. From this point of view, it is important to study not only balls, but also markers that show tubulo-interstitial changes early. Because the biological markers used in the early assessment of tubular dysfunction in relation to glomerular changes are not widely used in practice. Therefore, the use of uromodulin for this purpose can be one of the promising laboratory indicators confirming renal tubular dysfunction (regardless of the cause).